MACROECONOMIC VARIABLES AND STOCK MARKET PERFORMANCE IN NIGERIA - Kayode David Kolawole (Gusau Journal of Accounting and Finance, 2025)
This study examined macroeconomic variables and stock market performance in Nigeria, using secondary data from the Central Bank of Nigeria. The study adopted the Autoregressive Distributed Lag Model (ARDL) technique to analyze the data obtained for the study. Furthermore, the results revealed that exchange rate fluctuations significantly affect stock market performance with a p-value of (p<0.01). Interest rate is also significantly related to stock market performance, with a p-value of (p < 0.01). Inflation also significantly affects stock market performance with a p-value of 0.01. Finally, Gross Domestic Product significantly impacts the performance of the stock market in Nigeria with a coefficient value of (0.0000000137) and a p-value of (0.0269).  Based on the findings, the study concluded that macroeconomic fundamentals exert a substantial and measurable influence on stock market performance in Nigeria. Therefore, the study recommended that policymakers should implement strategies to stabilize the naira by promoting foreign investment, reducing overreliance on oil exports, and diversifying the economy.